Studi Eksperimental Pengaruh Substitusi Blotong terhadap Kuat Tekan Paving Block - Sabrina, Nabila; Alvian, Alvian; Sholichah, Mar'atus; Sulastriningsih, Ica (Politeknik Negeri Lhokseumawe, 2025)
Abstract — This experimental study evaluates the use of blotong as a substitute material in the manufacture of paving blocks without using gravel. This study prepared 6 samples, with 2 samples tested for compressive strength at 21 days and the other 4 samples tested for compressive strength at 28 days. The results of this study indicate an increase in the compressive strength of the paving blocks as the age of the test specimens increases, from 50–60 kN at 21 days to 45.89–147.86 kN at 28 days. In this study, one of the samples had the lowest compressive strength, namely sample 6 with 45.89 kN. Sample 6 was tested at 28 days, but still showed the worst compressive strength, which could be attributed to the consistency of the mixture, the consistency of compaction, or the material. All test specimens in this study failed to achieve the standards of SNI 03-0691-1996 for Class D paving blocks, as the water absorption and compressive strength values of the test specimens did not meet the minimum values specified in SNI 03-0691-1996. Keywords: blotong, paving block, compressive strength, water absorption, SNI- 03-0691-1996.